English as International Language Revisited: Implications on South Korea’s ELT Context - Fadhlur Rahman; Nizar Saputra (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
This paper specifically aims to examine conceptual and empirical studies on the evolution of English Language Teaching (ELT) worldwide and its progression affecting ELT in South Korea. A systematic review was used as the research methodology. A number of significant articles from top-tier journals and book chapters were analysed utilising a content analysis, to gain evidence-based solutions. This paper begins with the outset of EIL (English as an International Language) in general, and examines a paradigm shift concerning the prestige norms such as American English (AmE) and British Received Pronunciation (RP). This paper heavily emphasizes on the condition of English Language Teaching in South Korea, and what theoretical foundations can be utilized to English language program in South Korea. Furthermore, this paper critically investigates the interconnectedness complexities between English and the national language, along with the attitudes toward native and non-native English-speaking teachers. The findings reveal some particular recommendations which can be undertaken to reconceptualize the language policy, teachers’ recruitment and curriculum developments in South Korea.